The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1143/jpsj.78.103706
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Magnetic Monopoles in Spin Ice

Abstract: Excitations from a strongly frustrated system, the kagomé ice state of the spin ice Dy 2 Ti 2 O 7 under magnetic fields along a [111] direction, have been studied. They are theoretically proposed to be regarded as magnetic monopoles. Neutron scattering measurements of spin correlations show that close to the critical point the monopoles are fluctuating between high-and low-density states, supporting that the magnetic Coulomb force acts between them. Specific heat measurements show that monopole-pair creation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
155
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 21 publications
(63 reference statements)
3
155
0
Order By: Relevance
“…For this reason, spin ice offers a beautiful realisation of classical magnetostatics, with local violations of the ice rules entering as point magnetic charges (magnetic monopoles [11][12][13][14][15][16][17] ) and spin correlations which exhibit "pinch point" singularities in k-space…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, spin ice offers a beautiful realisation of classical magnetostatics, with local violations of the ice rules entering as point magnetic charges (magnetic monopoles [11][12][13][14][15][16][17] ) and spin correlations which exhibit "pinch point" singularities in k-space…”
Section: Introductionmentioning
confidence: 99%
“…By tiling these tiny magnets in specific geometrical arrangements, it is possible to create physical properties and functionalities not displayed by the constituent materials [1]. For instance, it has been recently demonstrated that artificial spin ice structures can display glass-like behaviour [3,4], configurable charge ordering [5] and topological structures that can be analogous to magnetic monopoles [6,7] and Dirac strings [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Its emerging gapless fractionalized excitations are called spinons 13 . The concept of fractional excitations has been applied to magnetic monopoles in spin ice [14][15][16][17] , kagome and hyper-kagome lattices 18 , the quantum Hall effect [19][20][21][22] , conducting polymers 23,24 , and even to certain spin arrays with local spin larger than 1/2 (refs 25, 26). For the prototypical spin-1/2 Heisenberg antiferromagnetic chain, exact calculations of the dynamic structure factor over the whole range of the spectrum have become available.…”
mentioning
confidence: 99%